Collection and Determination of Clinical Problems and Outcome Indicators of Expert Consensus on Clinical Application of Ethnic Medicine in the Treatment of Palpitation (Arrhythmia-premature Ventricular Complexes) - ZHANG Wenjie, LI Jun, CHEN Hengwen, TAN Yuqing, XIE Zicong, WU Ji, MENG Chao, LI Zhaoling, ZHANG Lesong (Zhongguo quanke yixue)
Background Ethnic medicine holds numerous advantages in the treatment of premature ventricular complexes (PVCs). However, there is a concerning trend of abuse of ethnic medicine, particularly in the absence of tailored clinical drug recommendations specifically designed for this purpose. Consequently, it is of crucial importance to standardize the diagnosis and treatment of PVCs within the context of ethnic medicine. Objective To establish the clinical problems and outcome indicators of the Expert Consensus on Clinical Application of Ethnic Medicine in the Treatment of Palpitation (Arrhythmia-Premature Ventricular Complexes) . Methods The inquiring experts were members of the consensus expert group, encompassing experts in the fields of cardiology, evidence-based medicine, and pharmacology. Specifically, within cardiology, they comprised multi-ethnic medical experts in traditional Chinese medicine, Tibetan medicine, Mongolian medicine, Uyghur medicine, Dai medicine, Korean medicine, and Zhuang medicine. Drawing from the available literature and expert interview reports, the research team conducted a comprehensive search of relevant literature on the treatment of PVCs using various ethnic medical practices. In April 2023, a series of one-on-one online interviews were conducted with 14 multi-ethnic medical experts. Following the integration of the interview results and expert experiences, the consensus steering committee and working group jointly drafted the initial proposals for clinical questions and outcome indicators, subsequently designing a survey questionnaire. Between May and July 2023, two rounds of questionnaire surveys were conducted, rigorously evaluating the positivity, concentration, coordination, and reliability of the questionnaire responses. Results The expert panel was characterized by its multidisciplinary collaboration, authority, and geographical representation. The two rounds of the Delphi method yielded a positive coefficient of 99.1%. For the five background questions, the mean score was greater than 4, with the full scale exceeding 40%. For the ten prospective questions, the mean score was greater than 3.9, with the full scale surpassing 35%. Additionally, the nine outcome indicators achieved a mean score greater than 7, with the full scale exceeding 30%. The mean coefficient of variation for these metrics was 14.9%, 16.3%, and 17.6%. The Kendall harmony coefficients for clinical questions and outcome indicators were 0.267 and 0.316. The chi-square test showed a P-value of less than 0.05. The Cronbach's α coefficients were 0.913 and 0.905, both exceeding 0.7, suggesting high reliability. Overall, the quality control results were satisfactory, indicating a high degree of credibility in the questionnaire design. Conclusion Utilizing the Delphi method, we have identified the clinical problems and outcome indicators that need to be addressed in the development of the Expert Consensus on Clinical Application of Ethnic Medicine in the Treatment of Palpitation (Arrhythmia-Premature Ventricular Complexes), laying a solid foundation for the subsequent formulation of the consensus.